The Influence of Perceived Service Quality and Product Assortment on Shopee Users’ Online Loyalty in Samarinda City - Riska Sari; Marsha Anindita; M. Risal (UNIVERSITAS PAKUAN, 2026)
The rapid growth of e-commerce in Indonesia has intensified competition among digital marketplace platforms in maintaining user loyalty. In Samarinda City, the increasing use of internet access and digital transactions indicates that online shopping behavior is developing significantly. However, user loyalty remains a critical challenge, particularly in relation to perceived service quality and product assortment. This study aims to examine the influence of perceived service quality and product assortment on the online loyalty of Shopee users in Samarinda City. A quantitative approach was employed using a survey method involving 100 Shopee users as respondents. The sampling technique used was simple random sampling, while data were analyzed using SPSS version 26 through validity testing, reliability testing, normality testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression, t-test, and coefficient of determination analysis. The results show that perceived service quality has a positive and significant effect on online loyalty, with a regression coefficient of 0.583 and a significance value of 0.000. Product assortment also has a positive and significant effect on online loyalty, with a regression coefficient of 0.335 and a significance value of 0.000. The R Square value of 0.757 indicates that perceived service quality and product assortment explain 75.7% of the variance in online loyalty, while the remaining 24.3% is influenced by other variables outside the research model. These findings imply that Shopee should continuously improve service quality, responsiveness, application stability, transaction security, and product diversity to strengthen long-term user loyalty. This study contributes to the development of digital marketing strategies, particularly in enhancing customer loyalty on e-commerce platforms in a local market context.